Calculation of Value At Risk using Historical Simulation, Variance Covariance and Monte Carlo Simulation Methods - Mahaputra, M. Rizky; Yandi, Andri; Maharani, Amalina (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
The purpose of this study is to measure the Value at Risk of single assets of companies listed on the Jakarta Islamic Index using the Historical Simulation, Variance Covariance and Monte Carlo Simulation methods. The research method is defined as a scientific way to obtain data with specific purposes and uses. The research design used in this study is a comparative study, this study uses data analysis methods with a quantitative approach. The results of the research are based on validity testing using the Backtesting Kupiec method and Basel traffic light known that all three methods are used in this study produces a valid (accurate) VaR value for used.